Does health literacy promote COVID-19 awareness? Evidence from Zhejiang, China - Chen, Chun; Xu, Tingke; Chen, Youli; Xu, Yue; Ge, Lizheng; Yao, Dingming; Zhang, Xuehai (Frontiers in Public Health, 2022)
Background: Health literacy (HL) is considered a crucial determinant of diseases prevention and control. However, the role of HL in the COVID-19 pandemic has not been studied using provincial representative data among Chinese residents. This study aimed to assess the association between HL and COVID-19 awareness among Zhejiang residents based on the 2020 China Health Literacy Survey. Methods: The study was conducted among 5,596 residents aged 15–69 in Zhejiang using multistage, stratified, probability proportional to size sampling. COVID-19 awareness and HL were assessed using the “Chinese Citizen Health Literacy Questionnaire (2020)” in Zhejiang. The covariates were divided into predisposing factors, enabling factors, and need factors according to Anderson’s model. Data were analyzed by the chi-square test and logistic regression. Results: The study showed the HL and COVID-19 awareness level of residents were 24.84% and 8.06% respectively in Zhejiang in 2020. After adjusting for covariates, residents with adequate health literacy were more likely to have better COVID-19 awareness (OR = 5.22, 95% CI = 4.13–6.59, p ＜ 0.001). Three dimensions of HL (knowledge and attitudes, behavior and lifestyle, and health-related skills) were associated with COVID-19 awareness. Additionally, COVID-19 awareness was associated with age, occupation, family size, annual household income, and chronic conditions. Conclusion: COVID-19 awareness is significantly associated with HL, suggesting that promoting health literacy is an important component of health education, disease prevention, and health promotion in response to the COVID-19 pandemic and even possible public health emergencies in the future.